Volcanic Structures and Magmatic Evolution of the Vesteris Seamount, Greenland Basin - Unger Moreno, Katharina A.; Thal, Janis; Bach, Wolfgang; Beier, Christoph; Haase, Karsten M. (Frontiers in Earth Science, 2021)
The formation of isolated seamounts distant from active plate boundaries and mantle plumes remains unsolved. The solitary intraplate volcano Vesteris Seamount is located in the Central Greenland Basin and rises ~3000 m above the seafloor with a total eruptive volume of ~800 km^3 . Here, we present a new high-resolution bathymetry of Vesteris Seamount and a detailed raster terrain analysis, distinguishing cones, irregular volcanic ridges, volcanic debris fans, U-shaped channels and lava flows. The slope angles, ruggedness index and slope direction were combined with backscatter images to aid geologic interpretation. The new data show that the entire structure is a northeast to southwest elongated stellar-shaped seamount with an elongated, narrow summit surrounded by irregular volcanic ridges, separated by volcanic debris fans. Whole-rock geochemical data of 78 lava samples form tight liquid lines of descent with MgO concentrations ranging from 12.6 to 0.1 wt. %, implying that all lavas evolved from a similar parental magma composition. Video footage from Remotely Operated Vehicle (ROV) dives shows abundant pyroclastic and hyaloclastite deposits on the summit and on the upper flanks, whereas lavas are restricted to flank cones. The seamount likely formed above a weak zone of the lithosphere possibly related to initial rifting parallel to the nearby Mohns Ridge, but the local stress field increasingly affected the structure of the volcano as it grew larger. Thus, we conclude that the evolution of Vesteris Seamount reflects the transition from deep, regional lithospheric stresses in the older structures to shallower, local stresses within the younger volcanic structures similar to other oceanic intraplate volcanoes. Our study shows how the combination of bathymetric, visual and geochemical data can be used to decipher the geological evolution of oceanic intraplate volcanoes.